2007
DOI: 10.2519/jospt.2007.2505
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass, Nonspecific Low Back Pain, and Anatomical Changes in the Lumbar Spine in Judo Athletes

Abstract: STUDY DESIGN: Cross-sectional study of a specific population. OBJECTIVES:To investigate the prevalence and coprevalence of nonspecific low back pain (nsLBP) and lumbar radiological abnormalities (LRA) in judo athletes.BACKGROUND: nsLBP and LRA occur frequently in judo athletes. High body mass has been reported to be associated with both nsLBP and LRA. METHODS AND MEASURES:The subjects comprised 82 male judo athletes (mean SD age, 20.1 0.9 years) from 3 weight categories: lightweight (n = 29), middleweight (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 27 publications
1
34
0
3
Order By: Relevance
“…Practicing judo can cause chronic injuries, especially those affecting the finger joints, the lower back and the ears 32 56 57…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Practicing judo can cause chronic injuries, especially those affecting the finger joints, the lower back and the ears 32 56 57…”
Section: Resultsmentioning
confidence: 99%
“…Okada et al 56 reported a prevalence of non-specific lower back pain (nsLBP) and lumbar radiological abnormalities (LRA) in elite Japanese judokas of 35.4% and 81.7%, respectively. The prevalence of LRA in the lightweight categories was lower than among middleweights and heavyweights and there was a higher coprevalence of LRA and nsLBP in the middleweight categories 56…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, such manual assessments may not reflect segmental spine movement in vivo (Landel et al 2008). While magnetic resonance imaging is an important diagnostic tool for identifying anatomical correlates of low back pain, it sometimes fails to differentiate between those with spine abnormalities and low back pain from those without low back pain (Iwai et al 2004;Okada et al 2007). Structural assessments are commonly used to diagnose injury, so their usefulness in assessing healthy athletes is limited.…”
Section: Assessing the Individualmentioning
confidence: 99%
“…In addition, only few studies [14,15] assessed the LBP prevalence in female athletes participated in the combat sports, while high mechanical loading (due to repetitive rotations and hyper extensions) on lumbar spine and the role this area plays as a source of dynamic power and static control of trunk could be a possible cause of low back pain in such sports [16].…”
Section: Introductionmentioning
confidence: 98%
“…Investigating the prevalence of LBP and its risk factors among different types of sports, particularly in special groups such as females, adolescents, and professionals could be beneficial regarding development of prevention strategies for LBP and its adverse consequences [9]. Unfortunately, many of earlier studies which addressed the prevalence of low back pain in athletes have a small sample size (fewer than 100 subjects) [15,[20][21][22]. Also, in other studies with larger sample size, the response rate was not high enough [5,23].…”
Section: Introductionmentioning
confidence: 98%